Pengaruh Bencana Covid-19, Pembatasan Sosial, pembatasan Fisik dan Strategi Pemasaran Online Pada Perilaku Konsumen Dalam Pembelian Produk Retail - Ming Ming Lukiarti; Agustina Widodo (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2022)
This study discusses the effect of four independent variables, namely the Covid-19 disaster, social restrictions, physical restrictions and online marketing strategies on the dependent variable, namely consumer behavior in purchasing retail products. The population in this study is retail product consumers in Rembang Regency, using purposive sampling method and taking a sample of 200 respondents. This study uses multiple regression analysis technique with SPSS 22 analysis tool, by calculating the relationship of the independent variables partially and simultaneously to the dependent variable and calculating the weight of the influence of the independent variable on the dependent variable with a determination test. The results of this study are, the COVID-19 disaster variable has a positive and insignificant effect on consumer behavior in purchasing retail products. While the social restriction variables, physical restrictions variables and online marketing strategy variables each partially have a positive and significant effect on consumer behavior in purchasing retail products. The variables of the COVID-19 disaster, social restrictions, physical restrictions and online marketing strategies simultaneously have positive and significant impacts. In the test of determination, the magnitude of the R2 coefficient of the three independent variables is 35.6%.